INDIA-CHINA TRADE RELATIONS: AN ANALYSIS - Begum, Asfika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Among the various regions with which India have trade relations; China has been the top trending partner of India. During the past decades, both India and China have expanded their trade significantly, and it has been crucial to sustaining their remarkable economic growth. However, an analysis with respect to their structural changes indicates many significant disparities. India is still a minor player in world trade, compared to China. This paper is an attempt to examine the trend, pattern and future prospects of trade relations between India and China using secondary data. The paper suggests that India’s trade deficit with China has been increasing over the years.